Structures of confinement in nineteenth-century asylums, using England and Ontario as a comparative study - Bartlett, Peter (Elsevier, 2000)
Traditionally, historians of the care of the insane have understood their work as a branch of medical history. This paper focuses instead on the administrative structures of nineteenth century asylums. These are geographically specific and historically contingent. The development of medico-legal discourse will depend on localized histories of medicine and law in individual jurisdictions concerned. In this paper, the legal structures of public asylums in Ontario and England in the mid-nineteenth century are taken as a case study of this approach. Consideration of the differences in administrative structures challenges the degree to which the institutions were understood in the same way in the nineteenth century, and can be understood as comparable by historians today: is it appropriate to refer to ‘the asylum’ as a coherent and consistent concept between jurisdictions in the nineteenth century. The answer may well be in the affirmative, but it will become clear that differences in administrative structures are significant, and as instructive as similarities.